We start by simplifying the radicals in the expression \( 6 \sqrt{175} + 7 \sqrt{28} \).
For \( \sqrt{175} \): \[ \sqrt{175} = \sqrt{25 \cdot 7} = \sqrt{25} \cdot \sqrt{7} = 5\sqrt{7} \] Thus, \( 6 \sqrt{175} = 6 \cdot 5 \sqrt{7} = 30 \sqrt{7} \).
For \( \sqrt{28} \): \[ \sqrt{28} = \sqrt{4 \cdot 7} = \sqrt{4} \cdot \sqrt{7} = 2\sqrt{7} \] Thus, \( 7 \sqrt{28} = 7 \cdot 2 \sqrt{7} = 14 \sqrt{7} \).
Now we combine the simplified terms: \[ 30 \sqrt{7} + 14 \sqrt{7} = (30 + 14) \sqrt{7} = 44 \sqrt{7} \]
The expression \( 6 \sqrt{175} + 7 \sqrt{28} \) simplifies to: \[ 44 \sqrt{7} \]
\(\boxed{44 \sqrt{7}}\)
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.